Association of Reduced Long-Lasting Insecticidal Net Efficacy and Pyrethroid Insecticide Resistance With Overexpression of CYP6P4, CYP6P3, and CYP6Z1 in Populations of Anopheles coluzzii From Southeast Côte d'Ivoire. (11th November 2020) - Meiwald, Anne; Clark, Emma; Kristan, Mojca; Edi, Constant; Jeffries, Claire L; Pelloquin, Bethanie; Irish, Seth R; Walker, Thomas; Messenger, Louisa A
Abstract: Background: Resistance to major public health insecticides in Côte d'Ivoire has intensified and now threatens the long-term effectiveness of malaria vector control interventions. Methods: This study evaluated the bioefficacy of conventional and next-generation long-lasting insecticidal nets (LLINs), determined resistance profiles, and characterized molecular and metabolic mechanisms in wild Anopheles coluzzii from Southeast Côte d'Ivoire in 2019. Results: Phenotypic resistance was intense: >25% of mosquitoes survived exposure to 10 times the doses of pyrethroids required to kill susceptible populations. Similarly, the 24-hour mortality rate with deltamethrin-only LLINs was very low and not significantly different from that with an untreated net. Sublethal pyrethroid exposure did not induce significant delayed vector mortality effects 72 hours later. In contrast, LLINs containing the synergist piperonyl butoxide, or new insecticides clothianidin and chlorfenapyr, were highly toxic to A. coluzzii . Pyrethroid-susceptible A. coluzzii were significantly more likely to be infected with malaria, compared with those that survived insecticidal exposure. Pyrethroid resistance was associated with significant overexpression of CYP6P4, CYP6P3, and CYP6Z1 . Conclusions: Study findings raise concerns regarding the operational failure of standard LLINs and support the urgent deployment of vector control interventions incorporating piperonyl butoxide, chlorfenapyr, or clothianidin in areas of high resistance intensity in Côte d'Ivoire. Abstract : Intense insecticide resistance is compromising malaria vector control in Côte d'Ivoire, driven principally by metabolic resistance mechanisms. Study findings support the urgent deployment of interventions incorporating newly approved insecticides and synergists to interrupt malaria transmission by insecticide-resistant vector populations.